THE READABILITY LEVEL OF READING PASSAGES ON ENGLISH TEXTBOOK FOR GRADE NINE IN INDONESIA - Eka Kusuma (Faculty of Education and Teachers Training, 2019)
Textbook is a major resource for students in teaching and learning process of English. The basic component of textbook is text. This is in line with text-based or genre-based approach applied by the K-13 curriculum in Indonesia. However, the publication from Ministry of Education (2016) in achievement of 15 year-old Indonesian students in Programme for International Student Assessment (PISA) shows that they did not have significant improvement in reading skill. One factor assumed is the readability level of reading passages on the textbook used in teaching and learning process. It is concerned with the level of difficulty from the text to be understood by the students. This study aims to investigate how the readability level of reading passages on English textbook for grade nine in Indonesia is. The writer uses “Think Globally Act Locally (2018 revision)” which is written and published by Ministry of Education in Indonesia. A descriptive qualitative research is employed in this study. There are three genres of reading passages in the book to be analyzed: procedure, narrative, and report text. The data was collected by documentation technique. To analyze the data, the writer used Flesch Reading Ease formula. This formula is the most widely used formula, the most tested, reliable, and the best in school text. The results of this study show that the readability level of 12 reading passages on English textbook for grade nine in Indonesia is varied. The range is from very easy to fairly difficult.